Opportunities and Challenges Facing Social Entrepreneurship in BRICS+ Countries - Samuel Bangura; Princess Thulile Duma; Ntombifuthi Alexia Mthembu (International Research Journal of Business Studies, 2025)
This study examined social entrepreneurship in the expanded BRICS+ countries, where rapid growth coexisted with persistent inequality, unemployment, and regulatory barriers. A systematic review of peer-reviewed literature was conducted to consolidate fragmented findings and to assess ecosystem maturity across member states. The study proposed a triangular framework connecting government, market, and community actors to support sustainable social impact. The review found that funding shortages and bureaucratic complexity remained major obstacles, while innovation, job creation, and hybrid organisational models created significant opportunities. Social ventures were found to contribute to poverty reduction and held potential to generate substantial economic value in comparable contexts. The study concluded that supportive policies were needed, including streamlined digital regulation, legal recognition of hybrid enterprises, expansion of impact investment, integration of social entrepreneurship into education, and cross-BRICS+ pilot programs led by more advanced ecosystems to enhance knowledge sharing and strengthen inclusive and sustainable development.